PANDEMIC: ADJUSTING SOCIAL WORK PRACTIUM. AN ISOLATED INDICENT OR AN ENTRY TO A LARGER DISCUSSION? - Choate, Peter; Tortorelli, Christina; Adams, Gina (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2022)
On March 13, 2020, Mount Royal University responded to the pandemic declaration of the World Health Organization (WHO) and local health directives by stopping all face-to-face learning, including practicums. This sudden cessation was done for reasons of safety and liability. Rapid shifts were required, presenting functional, ethical, and privacy challenges for students and faculty who recognized that practicums are vital for social work students preparing to enter practice. Using a theoretical framework of compounding complexity, the paper considers eight key learnings from the authors’ experiences managing a social work practicum program, contemplating implications for current and future crisis-oriented fieldwork. This paper goes further to challenge a re-evaluation of social work as a result of the pandemic, social movements including the Black Lives Matter movement, as well as the changing socio-economic factors that influence service users’ lives. These conversations have emerged within the pandemic context and afford a moment to reflect on the place and role of social work.